Investigation of 75-millimeter-bore cylindrical-roller bearings at high speeds. [Part] III, Lubrication and cooling studies - oil inlet distribution, oil inlet temperature, and generalized single-oil-jet cooling-correlation analysis - Macks, E. Fred.; Nemeth, Zolton N.; United States. (National Advisory Committee for Aeronautics, 1951)
Oil inlet distribution (5 methods were investigated) and oil inlet temperature (100 to 205 degrees F) were found to be significant factors in the cooling effectiveness of a given quantity of oil. Dimensional analysis was used to generalize the test-rig results so that it is possible to predict the inner- or outer-race temperatures above the oil inlet temperature from a single curve regardlesss of whether speed, load, oil flow, oil inlet temperature, oil-jet diameter or any combination of the parameters is varied.
NACA TN No. 2420
"July 1951."
Includes bibliographical references.
Oil inlet distribution (5 methods were investigated) and oil inlet temperature (100 to 205 degrees F) were found to be significant factors in the cooling effectiveness of a given quantity of oil. Dimensional analysis was used to generalize the test-rig results so that it is possible to predict the inner- or outer-race temperatures above the oil inlet temperature from a single curve regardlesss of whether speed, load, oil flow, oil inlet temperature, oil-jet diameter or any combination of the parameters is varied.
Keywords: Cooling. / http://id.loc.gov/authorities/subjects/sh85032186; Roller bearings / Testing.; Roller bearings / Lubrication. / http://id.loc.gov/authorities/subjects/sh85114874